Intercalating Graphite‐Based Na‐Ion Battery Anodes with Integrated Magnetite - Rukshan Karunarathna; Harsha Ranasinghe Arachchige; Shadeepa Karunarathne; W. Parakrama Sanjeewa Lakshitha Wijesinghe; Chanaka Sandaruwan; M. M. M. Prasanga Gayanath Mantilaka; Yasun Y. Kannangara; Amr M. Abdelkader (Small Science)
Graphite is known as the most successful anode material found for Li‐ion batteries. However, unfortunately, graphite delivers an ordinary capacity as anode material for the next‐generation Na‐ion batteries (SIBs) due to difficulties in intercalating larger Na+ ions in between the layers of graphene due to incompatible d‐spacing. The methodologies investigated in deriving suitable anode structures for SIBs are found to be either less effective, expensive, or rather too complex in most cases. Herein, a simple strategy is introduced to derive suitable anode materials for SIBs through a modified electrochemical exfoliation of graphite. The introduced exfoliation process is able to graft Fe3O4 (magnetite) on graphite allowing the structure to expand, supporting a swift intercalation and deintercalation of Na ions. The synthesized magnetite‐functionalized graphene nanoplatelets are identified as a well‐suited anode material for SIBs, with its efficient intercalation obtained through the expanded interlayer spacing of 3.9 Å and the surface redox pseudocapacitive activity attained through the surface‐grafted magnetite. The effectiveness of the synthesized is reflected in the obtained high discharge capacitance of 420 mAh g−1, with 96% capacitive retention over 1000 cycles. The study opens new opportunities for prospective low‐cost anode materials for energy storage applications.